2015
DOI: 10.1515/cse-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Solid Oxide Fuel Cell Cathodes: Importance of Chemical Composition and Morphology

Abstract: The main aspects of the cathode materials morphology for Intermediate Temperature Solid Oxide Fuel Cells (IT SOFC) are considered in this paper. The approaches for estimation of their basic properties, e.g. oxygen mobility and surface reactivity, are described and the results of different techniques (e.g. weight and conductivity relaxation, oxygen isotope exchange) application for studies of powders and dense ceramic materials are compared. The Ruddlesden-Popper type phases (e.g. Pr2NiO4) provide enhanced oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…In particular, solid oxide fuel cells (SOFCs) have been extensively studied and attracted much attention as a promising way to generate electricity at high efficiency and low cost [18][19][20]. For such applications, the cathode material must satisfy several criteria such as good electrical conductivity, high porosity to allow gas diffusion, thermal expansion coefficient matching well with that of the solid electrolyte, and chemical stability at a high temperature [21][22][23]. Most of the requirements listed above are satisfied by LaMnO 3 perovskites, making it one of the most suitable materials for cathode in SOFCs [24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, solid oxide fuel cells (SOFCs) have been extensively studied and attracted much attention as a promising way to generate electricity at high efficiency and low cost [18][19][20]. For such applications, the cathode material must satisfy several criteria such as good electrical conductivity, high porosity to allow gas diffusion, thermal expansion coefficient matching well with that of the solid electrolyte, and chemical stability at a high temperature [21][22][23]. Most of the requirements listed above are satisfied by LaMnO 3 perovskites, making it one of the most suitable materials for cathode in SOFCs [24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different studies revealed different values for oxygen flux using different approaches for LSCF production with a stoichiometric ratio composition. [119,120] For instance, four methods, namely, coprecipitation (CP), solid-state reaction (SS), spray-pyrolysis (SP), and citrate acetate (CA) were used to synthesize La 0.8 Sr 0.2 Co 0.6 Fe 0.4 O 3 membranes with the aim to investigate the effect of these methods on the microstructure and composition, and ultimately the electrical conductivity of the membranes. The observed density for all the membranes were found to be 97 % of the theoretical value.…”
Section: Effects Of Synthesis Techniques On the Preparation Of Lscf-b...mentioning
confidence: 99%
“…The Ruddlesden–Popper (RP) phases with the general formula of (AO)(ABO 3 ) n or A n+1 B n O 3n+1 consist of the perovskite layers ABO 3−δ alternating with the rock salt layers A 2 O 2+δ [ 58 , 60 , 63 , 69 , 129 , 159 , 285 , 286 , 287 , 288 , 289 , 290 ]. The important feature of RP phases, which makes them attractive SOFC cathodes and oxygen-separation-membrane materials, is a fine oxygen transport provided via the cooperative mechanism of oxygen migration.…”
Section: Oxygen and Hydrogen Mobility Of Materials For Membranes And ...mentioning
confidence: 99%
“…The important feature of RP phases, which makes them attractive SOFC cathodes and oxygen-separation-membrane materials, is a fine oxygen transport provided via the cooperative mechanism of oxygen migration. In this case, both lattice and interstitial oxide anions accumulating at a high level are involved in the process of oxygen transport ( Figure 20 ) [ 55 , 58 , 60 , 63 , 69 , 159 , 285 , 288 , 291 , 292 , 293 , 294 , 295 , 296 , 297 ]. This allows them to reach superior oxygen mobility compared to other MIECs ( Figure 21 ).…”
Section: Oxygen and Hydrogen Mobility Of Materials For Membranes And ...mentioning
confidence: 99%
See 1 more Smart Citation